Mathematical Modelling as an Emissary of Mathematics Proficiency: A Case of the BED Mathematics Students at a University in Zimbabwe - Chipo Makamure (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2026)
A central argument supporting a specific approach to mathematics education is that students learn effectively by engaging in their own investigations of complex situations, formulating mathematical interpretations and that educators should facilitate these experiences, allowing students to take ownership of their learning. In contrast, an alternative perspective presented in the literature argues that mathematics is a universal and timeless discipline. According to this view, students acquire knowledge primarily through the absorption of clearly articulated concepts, necessitating that educators provide explicit explanations followed by structured opportunities for students to connect, practice, and solidify their understanding. The challenge associated with these positions does not stem from a simplistic dichotomy of truth versus falsehood, rather, it is rooted in their inherent incompleteness. Both viewpoints inadequately engage with the complex nature of mathematics. This study aims to address the frequently posed question among mathematics educators: “What type of mathematics education is necessary for students to acquire mathematical knowledge and thinking skills that can be applied in real-life situations?” This is a qualitative study, guided by the Theory of Didactic Situations (TDS) which discusses a theoretical foundation for the mathematical modelling approach in the contexts of teaching and learning, spelling out its significance in fostering mathematical understanding. Additionally, the study references empirical examples drawn from the work of students at higher education institutions in Zimbabwe, illustrating how the mathematical modelling approach to mathematics education can enhance mathematical proficiency. Generally, this study found that Mathematical modelling provided a good opportunity for students to employ more of their senses in building mathematical concepts. Despite the challenges inherent in mathematics modelling, these challenges can be effectively addressed when educators prioritise the diverse pathways available for student learning. In conclusion, it is insufficient to assess students' proficiency in mathematics solely through theoretical questions. True mastery is demonstrated when students can implement the concepts they have learned in practical situations, embodying the essence of mathematics modelling.